2004
DOI: 10.1111/j.1365-2885.2004.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple oral dosing of ketoconazole influences pharmacokinetics of quinidine after intravenous and oral administration in beagle dogs

Abstract: In this study, we investigated the effect of multiple oral dosing of ketoconazole (KTZ) on pharmacokinetics of quinidine (QN), a CYP3A substrate with low hepatic clearance, after i.v. and oral administration in beagle dogs. Four dogs were given p.o. KTZ for 20 days (200 mg, b.i.d.). QN was administered either i.v. (1 mg/kg) or p.o. (100 mg) 10 and 20 days before the KTZ treatment and 10 and 20 days after start of KTZ treatment. Multiple oral dosing of KTZ decreased significantly alpha and beta, whereas increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
(24 reference statements)
1
15
0
Order By: Relevance
“…Ketoconazole can competitively inhibit CYP3A12 activities [19] and at a therapeutic dose can largely decrease the total body clearance of the CYP3A substrates such as midazolam and nifedipine. Therefore, the beagle dog can be used as an animal model to predict drugdrug interactions between ketoconazole and CYP3A substrates in clinical practice [20] . Kyokawa et al [17] reported that the beagle dog can be a suitable animal model for predicting the induction of both hepatic and intestinal CYP3A in humans.…”
Section: Pharmacokinetics Of Gls4 Affected By Rifampicinmentioning
confidence: 99%
“…Ketoconazole can competitively inhibit CYP3A12 activities [19] and at a therapeutic dose can largely decrease the total body clearance of the CYP3A substrates such as midazolam and nifedipine. Therefore, the beagle dog can be used as an animal model to predict drugdrug interactions between ketoconazole and CYP3A substrates in clinical practice [20] . Kyokawa et al [17] reported that the beagle dog can be a suitable animal model for predicting the induction of both hepatic and intestinal CYP3A in humans.…”
Section: Pharmacokinetics Of Gls4 Affected By Rifampicinmentioning
confidence: 99%
“…This extent was similar to those in hepatic microsomes from dogs treated with DEX in our previous study. Since QN is mainly metabolized by CYP3A [11] and is categorized as a drug with low hepatic extraction [2], our present study suggests that DEX treatment at clinical doses significantly decreases CYP3A activity, even in intact dogs, and thereby significantly alters the pharmacokinetics of the CYP3A substrate.…”
Section: Discussionmentioning
confidence: 66%
“…Because of this, we examined the effect of clinical doses of DEX on the pharmacokinetics of a CYP3A substrate, quinidine (QN), in dogs. We selected this drug because it is mainly metabolized by CYP3A [11] and is subjected to low hepatic extraction in dogs [2]. …”
mentioning
confidence: 99%
“…Interactions in dogs involving ketoconazole have previously been attributed to CYP3A pathways (Kuroha et al, 2002a(Kuroha et al, , 2004. In particular, the human ketoconazole-midazolam interaction is very established so it is usually the first substrate/inhibitor pair to be tested in vitro with liver microsomes from lesser characterized species.…”
Section: Discussionmentioning
confidence: 99%